5(x+2)-7=5(2x+3)-1

Simple and best practice solution for 5(x+2)-7=5(2x+3)-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+2)-7=5(2x+3)-1 equation:


Simplifying
5(x + 2) + -7 = 5(2x + 3) + -1

Reorder the terms:
5(2 + x) + -7 = 5(2x + 3) + -1
(2 * 5 + x * 5) + -7 = 5(2x + 3) + -1
(10 + 5x) + -7 = 5(2x + 3) + -1

Reorder the terms:
10 + -7 + 5x = 5(2x + 3) + -1

Combine like terms: 10 + -7 = 3
3 + 5x = 5(2x + 3) + -1

Reorder the terms:
3 + 5x = 5(3 + 2x) + -1
3 + 5x = (3 * 5 + 2x * 5) + -1
3 + 5x = (15 + 10x) + -1

Reorder the terms:
3 + 5x = 15 + -1 + 10x

Combine like terms: 15 + -1 = 14
3 + 5x = 14 + 10x

Solving
3 + 5x = 14 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
3 + 5x + -10x = 14 + 10x + -10x

Combine like terms: 5x + -10x = -5x
3 + -5x = 14 + 10x + -10x

Combine like terms: 10x + -10x = 0
3 + -5x = 14 + 0
3 + -5x = 14

Add '-3' to each side of the equation.
3 + -3 + -5x = 14 + -3

Combine like terms: 3 + -3 = 0
0 + -5x = 14 + -3
-5x = 14 + -3

Combine like terms: 14 + -3 = 11
-5x = 11

Divide each side by '-5'.
x = -2.2

Simplifying
x = -2.2

See similar equations:

| [6-3n]-3=27 | | p^2-8p*21=6 | | -3(+5)=8X+18 | | 7000x-14000(x+0.5)=595 | | -3.1+5.9+(-10)+3= | | sqrt(3m+4)=m | | 5a^2*1/6 | | 3(2x-1)+5=32 | | 5=1+2x | | 24x-7-16x+3=23x-8-15x+13 | | 4x-2(x-3)=x+12 | | 7(p+2)-4p=3p+14 | | 100y+300x*40=8400 | | 7/9*1/5*3/35 | | -1/6-6 | | -2/9*-1/4 | | [3+4x]=15 | | 100+300*40=8400 | | 21/1575 | | 2(v-3)-7=-3(-5v+1)-5u | | C/6=4 | | -4(-5w+6)-7w=5(w-5)-9 | | 2n+10=107.50 | | (-2/4)x+3=1 | | 142+2.7x=300 | | 7(n-2)-6=2n+8+n | | 900x=10 | | 2(x-.5)-6x= | | 142+2.7x=40 | | x+5-8=-2 | | -5(2w-6)+w=3(w+8) | | 3000x-6000(x+0.3)=93 |

Equations solver categories